Edukasi SADARI dalam Mendeteksi Dini Kanker Payudara pada Kelompok Dharma Wanita Kementerian Agama Kabupaten Ciamis - Elis Roslianti; Yanti Srinayanti; Neli Sunarni (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Breast cancer is a condition where there is malignant tissue or tumor in the breast tissue which if not treated immediately will cause death. BSE is a method that can be done independently for early detection of breast cancer. Objective: The aim of this health education is to increase knowledge in early detection of breast cancer in women of reproductive age. Method: This community service was carried out at the Ministry of Religion of Ciamis Regency with participants from the Dharma Wanita Ministry of Religion of Ciamis Regency. The method used is the observational method, seminars and questions and answers that begin with conducting a survey to determine the location and targets. Then arrange materials, materials and training in the form of slides and papers to be presented to participants. Results: Implementation of this health education to Dharma Wanita women of the Ministry of Religion of Ciamis Regency as participants and carried out at the Religious Office of the Ministry of Religion of Ciamis Regency to increase women's knowledge and awareness in early detection of breast cancer. Conclusion: BSE health education in early detection of breast cancer conducted optimally.